Differences in the Application of the Right of Ijbar Based on Fiqh and Law No. 39/1999 on Human Rights - Prastio, Ary Darma; Lubis, Fauziah (Universitas Islam Sultan Agung, 2023)
This study aims to find out about the differences in the application of ijbar rights according to fiqh and Law No.39 of 1999 concerning Human Rights, how the legal rules of ijbar rights based on fiqh and Law No.39 of 1999, whether the application of ijbar rights based on fiqh and Law No.39 of 1999 is in line, whether there is special protection for women who are forced to marry by guardians, what are the negative impacts of the application of ijbar rights on the harmony of a marriage. The research method used is library research. Many guardians abuse the right of ijbar and lead to forced marriage, while according to Law No.39 of 1999 a child also has full rights over his survival, one of which is to choose his life partner. With regard to the provisions of the mujbir guardian, the majority of fiqh scholars, such as the maliki, shafi'i, and hambali circles allow the right of ijbar by a guardian to a child or person under his guardianship to marry even without the child's permission, this is very contrary to Law No.39 of 1999.